Various aspects of radiosurgery – a review - Kozikowska, Marta; Kmak, Bożena; Szot, Anna (Quality in Sport, 2024)
Introduction and purpose Radiosurgery (RS) is an innovative treatment method that involves the precise administration of a large dose of ionizing radiation to the diseased area of ​​the body sparing healthy tissues maximally. The treatment is non-invasive and usually painless for the patient, and its greatest advantage is the immediate destruction of cancer cells. The method enables the treatment of tumors which are located within the brain tissue, but also of extracranial lesions in almost all organs of the human body. The aim of this article is to compare the structure, principles of operation, advantages, disadvantages and the use of Gamma Knife and CyberKnife in neurosurgery. These devices are used to perform radiosurgery and stereotactic radiotherapy procedures. They are an alternative to neurosurgical procedures, especially for cancerous tumors located in hard-to-reach places, and significantly reduce the risk of postoperative complications. Materials and methods The literature included in the PubMed, BioMed Central and Polish Medical Platform databases is searched by means of the words such as Gamma Knife, CyberKnife, radiosurgery, stereotactic radiotherapy. Quoted sources in selected works were also used. Conclusions Stereotactic radiosurgery is an element of radical, palliative or analgesic treatment of well-circumscribed small lesions, less than 5 cm in diameter. Gamma Knife and CyberKnife enable cancerous and non-cancerous treatment lesions. Both procedures are performed on an outpatient basis and are considered minimally invasive procedures, especially recommended for patients who cannot undergo neurosurgical surgery or require less invasive cancer treatment. Gamma Knife was designed for radiosurgery of lesions located intracranially and covering the upper parts of the cervical spine up to the level of the fourth cervical vertebra, while CyberKnife or modern linear accelerators are used for intracranial and extracranial radiosurgery.